Improving Elementary School Students Mathematical Problem Solving Abilities with the REACT Learning Strategy - Fendrik, Muhammad; Syahrilfuddin, Syahrilfuddin; Ulfah, Salsabil (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The purpose of this study is to determine the effect of the REACT learning strategy on problem-solving among fifth-grade students at Pekanbaru Public Elementary School. This type of research employs a quasi-experimental approach with a nonequivalent group control group design. This study employs a purposive sampling technique, in which samples are chosen based on specific criteria. This study employs two classes: VA as the experimental class and VB as the control class. The experimental class received treatment (treatment), while the control class did not. Data collection methods include test instruments and documentation. The significant results (2-tailed) of 0.013 < 0.05 indicate that REACT strategy learning has an effect on problem-solving ability, leading to the acceptance of Ha and rejection of H0. Based on these findings, it is possible to conclude that the REACT learning strategy (relating, experiencing, applying, cooperating, and transferring) has an effect on fifth-grade students’ problem-solving abilities.